Characteristics of soil nitrogen and nitrogen cycling microbial communities in different alfalfa planting years - Xu, Fujin; Wu, Jie; Ru, Liyang; Chang, Huiqing (Archiv für Acker- und Pflanzenbau und Bodenkunde, 2023)
Nitrogen cycling in soil and its microbial community characteristics are closely related. Characteristics of soil nitrogen, community diversity of nitrogen-fixing bacteria (NFB) and ammonia oxidizers were study with a traditional farmland as control and five treatment alfalfa fields of 1-, 2-, 3-, 4- and 5-year (a) cultivation. The results showed that total nitrogen (TN) significantly increased in 3, 4 and 5 a, alkali-hydrolysable nitrogen (AHN), NH 4 + -N (AN), NO 3 − -N (NN) and SOC was the highest in 3, 5, 3, 4 a, respectively. The dominant phylum of NFB and ammonia-oxidizing bacteria (AOB) belonged to Proteobacteria with a higher diversity and abundance in 3 and 4 a. Crenarchaeota was found the dominant phylum of ammonia-oxidizing archaea (AOA) with the highest abundance in the alfalfa field planted for 2 a. The dominant genus of NFB and AOB were Azohydromonas and Nitrosospira, respectively, which showed the highest abundance in the alfalfa fields planted for 2 and 3 a, respectively. The diversity of NFB and AOB showed a significantly positive correlation with TN and AHN (p < 0.05). AOA showed a significantly negative correlation with AN (p < 0.05). Many microbial species cannot be annotated in this study, which deserves future investigation.